(untitled) (Journal of Atomic and Molecular Sciences, 2016)
By solving the time-dependent Schrödinger equation (TDSE) accurately with time-dependent generalized pseudospectral (TDGPS) method, we theoretically investigated the high-order-harmonic generation (HHG) from three dimensional (3D) Hydrogen atom in ultraviolet (UV)-assisted chirped fields. When a 128 nm UV pulse is added on a chirped fundamental field, the HHG spectra is greatly broadened and enhanced, which is quite similar as the HHG from H atom initially prepared in the first excited state in the chirped field only. Besides, the HHG of H atom in the combination of a chirped fundamental field and a 256 nm UV pulse case is also investigated. The HHG process is illustrated by the semi-classical three-step model and the time-frequency analysis. The ionization probability and electron wavepacket as functions of time are also calculated to further illustrate this phenomenon. Furthermore, we also discuss the influence of time delay between the chirped fundamental field and the 128 nm UV pulse on HHG process. Finally, by superposing the harmonics in the range of 200th-260th order, an isolated attosecond pulse with a duration of about 64 as can be generated.